Lap Joint on St.37 Steel Plate with Friction Welding Clamping Method - Setiawan, Widia; Santoso, Nugroho; Wiyadi, Wiyadi; Aji, Muhammad Sulistiyo; Alamin, Rachmat; Tarmudi, Achsan (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
Friction stir (FW) welding is a relatively fresh method that was created and has been continually refined and adapted to industrial applications due to its benefits. This approach for solid-state joining entails connecting the components at a temperature below their melting point and then heating them up. Clamp joint applications are widely used using external heating and hitting with high strength, but the clamped joints with the FW method are rarely done. The research studied the characteristic of clamped joints at various plate thicknesses using the FW method. In this study, 30 specimens were used in the form of a St.37 low carbon steel plate with a size of 50 mm x 100 mm and a thickness of 3 mm, 5 mm, and 9 mm, and several holes were made with a diameter of 5 mm. The plate was connected by 2 clamps, and 4 clamps then the FW method was conducted in a milling machine. The results indicate that the plates were connected well. The highest hardness value was 256.4 VHN on the FW of 9 mm plate. The microstructure is dominated by ferrite and a little pearlite phase. The largest shear force is 66.54 kN obtained at 4 clamps with a plate thickness of 9 mm, and the lowest is 13.46 kN, obtained at 2 clamps with a plate thickness of 3 mm.